1987
DOI: 10.1099/00222615-24-3-241
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative bacteriology of the vaginal flora during the menstrual cycle

Abstract: Summary. The vaginal bacteriology of 10 healthy asymptomatic women was assessed during the menstrual cycle. Samples were taken from the posterior vaginal fornix for quantitative analysis. There were no significant alterations in the total vaginal flora at different stages of the menstrual cycle. The mean number of species isolated per specimen declined from 4.6 in week 1 to 2-9 in week 4. This decline was not caused by a decrease in the occurrence or concentration of any one organism or group of organisms. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 12 publications
(6 reference statements)
2
20
0
Order By: Relevance
“…Taken in sum, these data suggest the following: (i) there are distinct differences in the identities of the numerically dominant populations, thus suggesting that there is more than one kind of "normal" microbial community found in healthy women; (ii) the structures of the communities (at least as reflected by the most abundant populations) were comparatively invariant over time; and (iii) some communities (women 1 and 5) have phylotypes other than lactobacilli among the dominant populations. Conclusions i and ii are consistent with those of previous studies (3,19,30,53), whereas this represents the first instance where populations other than lactobacilli have been shown to be numerically dominant in the vaginal communities of healthy women. Additional studies are needed to verify this observation, since only a small number of women were included in this study.…”
Section: Optimization Of T-rflpsupporting
confidence: 81%
See 1 more Smart Citation
“…Taken in sum, these data suggest the following: (i) there are distinct differences in the identities of the numerically dominant populations, thus suggesting that there is more than one kind of "normal" microbial community found in healthy women; (ii) the structures of the communities (at least as reflected by the most abundant populations) were comparatively invariant over time; and (iii) some communities (women 1 and 5) have phylotypes other than lactobacilli among the dominant populations. Conclusions i and ii are consistent with those of previous studies (3,19,30,53), whereas this represents the first instance where populations other than lactobacilli have been shown to be numerically dominant in the vaginal communities of healthy women. Additional studies are needed to verify this observation, since only a small number of women were included in this study.…”
Section: Optimization Of T-rflpsupporting
confidence: 81%
“…The microflora of the lower genital tract in women has been studied in a variety of human populations by using different bacterial isolation and identification techniques (4,21,30,34,53). In healthy women, vaginal communities are typically dominated by various species of lactobacilli that number approximately 10 8 CFU per ml (or g) of vaginal secretion.…”
mentioning
confidence: 99%
“…Furthermore, vaginal flora are dynamic, and the level of lactobacilli measured in the present study may not reflect the level of lactobacilli present when the participant was infected with T. vaginalis; however, a study of vaginal flora has shown that the level of lactobacilli does not significantly change during the menstrual cycle [14].…”
mentioning
confidence: 76%
“…LB may also inhibit opportunist bacteria through the production of bacteriocins, immune stimulation and via nutrient and stearic competition. There is also substantial interest in the role of hydrogen peroxide (H The normal vagina has a pH of 3.5 -6.0 [4] and is anaerobic, with pO 2 and pCO 2 lower and higher, respectively, than atmospheric levels; menstruation increases pH [9,12] and oxygen tension [8]. Studies of LB characteristics that may protect the vagina should address these conditions.…”
mentioning
confidence: 99%